Bioimmobilization of lead by Bacillus subtilis X3 biomass isolated from lead mine soil under promotion of multiple adsorption mechanisms. Issue 2 (6th February 2019) - Qiao, Weichuan; Zhang, Yunhao; Xia, Hao; Luo, Yang; Liu, Si; Wang, Shiyu; Wang, Weihan
Abstract : In this study, a lead-resistant bacterium, Bacillus subtilis X3, was used to prepare a lead bioadsorbent for immobilization and removal of lead in lead solution. The lead shot precipitate was analysed by scanning electron microscopy combined with energy dispersive X-ray fluorescence microscopy, Fourier transform infrared spectroscopy, X-ray diffraction and X-ray photoelectron spectroscopy. The adsorbed lead was mainly mineralized to form Pb5 (PO4 )3 OH, Pb10 (PO4 )6 (OH)2 and Pb5 (PO4 )3 Cl; however, other mechanisms that can also promote the mineralization of lead should not be ignored. For example, Na + and Ca 2+ on the cell wall surface were exchanged with Pb 2+ in solution, which confirmed that the ion-exchange process occurred before mineralization. Moreover, adsorption bridging caused by extracellular polymeric substances also accelerated the further aggregation of lead, and the biomass was encapsulated by lead gradually. Hydroxyl, carbonyl, carboxyl and amine groups were not observed in lead mineral crystals, but the complexation between lead and these groups still benefited the mineralization of lead. The valence of Pb(II) was not changed after mineralization, which indicated that the biosorption process was not a redox reaction. Finally, biosorption occurred on the outer surface of the cell, but its specific surface area was relatively small, limiting the amount and efficiency of biosorption.